PENGENDALIAN HAYATI PENYAKIT DARAH PADA PISANG DENGAN PSEUDOMONAD FLUORESEN DAN Bacillus spp. - Nur Edy (Agroland: Jurnal Ilmu-ilmu Pertanian, 2011)
Four antagonist bacterial strains, Pseudomonad fluorescent strain UTD1 (Pf-UTD1), Pseudomonad fluorescent strain UTD2 (Pf-UTD2), Bacillusspp. strain UTD1 (Ba-UTD2), and Bacillusspp. strain UTD1 (Ba-UTD1) which had been found  to have biocontrol activity  in vitro assays against blood disease bacteria, the causal agent of wilt banana, were tested for their compatibility in vitro and its antagonism  in  screen  house using  banana  budless  Kepok  as  test  plant.  The compatibility  test showed  that  Pseudomonad  fluorescent strain  UTD1  was  only  compatible  with Pseudomonad fluorescent strain UTD2, Pseudomonad fluorescent strain UTD2 compatible with all antagonist (Pf-UTD1, Ba-UTD1, dan Ba-UTD2), Bacillus  spp.  strain UTD1 only compatible with Bacillus  spp. strain UTD2,  and Bacillus spp.  strain UTD2  compatible with all  antagonist  (Pf-UTD1, Pf-UTD2 and  Ba-UTD1).  Inoculation  with  blood  disease bacteria  caused  significant  wilting,  and  reduced plant growth.  Single  Inoculation  using  either  Pseudomonad fluorescent  UTD1  or  Bacillus  spp. UTD2  causing  greater results with  no wilting. Combination  between Pseudomonad fluorescent UTD2 and Bacillus spp. UTD2 also  showed no wilting. Generally, all treatments were considered good because  they  could  reduce  disease  intensity  less  than 25%,  except  for  Pseudomonad fluorescent UTD2  and Bacillus  spp. UTD  treatments which  caused wilting  up  to 38.89%.    The results suggested  that both single and combination  treatments of Pseudomonad  fluorescent UTD2 and Bacillus spp. UTD2 can be used to control blood disease bacteria in wider scale.  Key words: Bacillus spp., biological control, blood disease bacteria, pseudomonad fluorescent.